2021
DOI: 10.1364/oe.432183
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-zoom bifocal metalens by mutual motion of cascaded bilayer metasurfaces in the visible

Abstract: Metalens, a subcategory of metasurfaces, has been widely investigated by virtue of its miniature and ultrathin characteristics as well as versatile functionalities. In this study, a tunable bifocal metalens with two continuous-zoom foci is proposed and numerically verified. This design utilizes two cascaded layers of metasurfaces, and different phase profiles for incidences of opposite helicities are imparted on each layer by the combination of geometric phase and propagation phase. When two layers of metasurf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…TBML combines geometric phase ψ and propagation phase η. It is known that geometric metasurfaces impart opposite phase distributions for LCP and RCP incidences by rotating unit cells 23 , and propagation phase depends on the geometric parameters of the unit cells and insensitive to the polarization states of the incident light [26][27][28] . Assume a circularly polarized beam is incident on a nanostructure of geometric metasurfaces, the transmitted light can be expressed as = exp( 2 ) -, 22…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…TBML combines geometric phase ψ and propagation phase η. It is known that geometric metasurfaces impart opposite phase distributions for LCP and RCP incidences by rotating unit cells 23 , and propagation phase depends on the geometric parameters of the unit cells and insensitive to the polarization states of the incident light [26][27][28] . Assume a circularly polarized beam is incident on a nanostructure of geometric metasurfaces, the transmitted light can be expressed as = exp( 2 ) -, 22…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…Up to now, diverse metalenses have been proposed and demonstrated, including spin-controllable metalens [22,23], achromatic metalens [24,25], tunable metalens [26,27] and long focal depth metalens [28,29], etc. It is well known that the multi-foci metalens can play important role in the applications of optical tomography technology, optical data storage, optical communication and photoelectric detection [30][31][32]. In 2015, Chen et al demonstrated a circular polarization sensitive longitudinal threefoci metalens made of gold nanorods by dividing a complete metalens into three annular bands, every annular band corresponds to a focal point [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, people have tended to manufacture metalenses with a variable focus to meet various applications and needs rather than being limited to a fixed focus. As a result, various forms have emerged in the study of variable focus metalenses: mechanically stretching the substrate [25][26][27], adjusting the mutual angle between two chiral metasurfaces [28,29], driving the geometrical position between two separate metalenses [30,31], and exploiting a micro-electromechanical-system (MEMS)-integrated metasurface [32][33][34]. The disadvantage is that these zoom metalenses need to be mechanically stretched or moved to achieve the zooming function, and problems such as easy damage, serious mechanical wear, low yield, and a complex overall device structure may occur.…”
Section: Introductionmentioning
confidence: 99%